Improving Quality of Life (IntechOpen, 2023)
The authors of this volume provide a window into what influences the quality of life, why people live longer, and why we are relatively better off compared to decades ago. While the potential ways of measuring life quality are abundant, understanding what causes improvement requires careful study and consideration. This volume provides useful insight into these challenges and helps to highlight a clear and important separation between wellbeing and standard of living, both relevant to assessing the quality of life. Standard of living refers to the material welfare of a group. Wellbeing, on the other hand, encapsulates harder-to-measure subjective preferences. Together they help us to understand the quality of life of certain groups at specific times, and in specific communities.